Exposure of New Zealand-Listed Firms to Global Risks - Huynh, Linh Chi (Auckland University of Technology, 2026)
Motivated by rising global risks, this dissertation investigates how exchange rate and geopolitical risks are transmitted to firms in a small open economy by examining stock return exposure to these risks among New Zealand-listed companies. Using daily stock returns for 147 non-financial firms over 2012–2025, we first estimate firm-level sensitivities to exchange rate and geopolitical risks, followed by an analysis of how firms’ international operations and risk management practices shape these exposures, and a test of whether geopolitical risk can aggravate firm-level exchange rate exposure. We find that at the aggregate level, appreciations of TWI, CNY, and USD, as well as increases in geopolitical risk, are associated with lower stock returns for New Zealand firms. At the firm level, only around 10–15% of firms exhibit statistically significant exchange rate exposure, and approximately 9–11% show significant sensitivity to geopolitical risk. Cross-sectional analysis shows that larger firms exhibit greater exposure to currencies of New Zealand’s major trading partners. Export-oriented firms show greater sensitivity to AUD returns, while firms with stronger operational links to Australia exhibit significantly lower exposure to both AUD and TWI movements, consistent with operational hedging. These firms also show significantly greater sensitivity to geopolitical risk. There is no evidence that financial hedging reduces exposure to either exchange rate or geopolitical risks. We further find that geopolitical risk has a direct negative effect on firm-level exchange rate exposure but does not amplify it, with the only exception of AUD exposure increasing for firms reporting higher hedging activity during periods of elevated geopolitical risk. The findings suggest that firm-level exposure to global risks is shaped more by operational and geographic structures than by financial hedging. The results imply that risk managers of New Zealand-listed firms should prioritise strategic operational alignment and geographic diversification over traditional financial hedging instruments when managing exposure to both currency fluctuations and geopolitical volatility.